Paradigma Daktiloskopi Kontemporer: Antara Efisiensi Administrasi dan Privasi Warga Negara - Ferry Candra; Ratna Artha Windari; Oloan C.H Marpaung (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study discusses the contemporary paradigm of non-criminal fingerprint use in Indonesia by highlighting the dialectic between state administrative efficiency and the protection of citizens’ privacy. Through an interdisciplinary approach integrating technical, legal, and social perspectives, this research analyzes the implementation of e-KTP, which has recorded more than 270 million citizens in a centralized biometric database, as well as the expansion of fingerprint usage in banking, telecommunications, e-SIM, and various other public service sectors. The analysis results indicate that non-criminal fingerprinting provides significant benefits in improving operational efficiency, preventing fraud, and strengthening security. However, its implementation also creates serious privacy risks, including the irreversible nature of biometric data, vulnerability to spoofing, single-modal system accuracy ranging from 87–92%, and the potential for mass surveillance. Law Number 27 of 2022 on Personal Data Protection represents an important advancement in the national legal framework; however, its implementation still faces challenges due to the lack of an optimal independent supervisory authority and incomplete implementing regulations. This study recommends strengthening data governance, implementing privacy by design, adopting multimodal biometrics, ensuring transparency in data management, limiting usage based on the principle of proportionality, improving digital literacy, and harmonizing regulations with international standards to maintain a balance between technological innovation and citizens’ fundamental right to privacy.